Review of the lady beetle genus Phaenochilus Weise (Coleoptera: Coccinellidae: Chilocorini) with description of a new species from Thailand that preys on cycad aulacaspis scale, Aulacaspis yasumatsui Takagi (Hemiptera: Sternorrhyncha: Diaspididae) - Giorgi, José Adriano; Vandenberg, Natalia J. (Zootaxa, 2012)
Species of the genus Phaenochilus are reviewed, keyed, and illustrated, and an annotated checklist provided. A newspecies, Phaenochilus kashaya n. sp., is described from Thailand. This species feeds on an invasive pest of cycads, thecycad aulacaspis scale, Aulacaspis yasumatsui Takagi (Hemiptera: Sternorrhyncha: Diaspididae). The economic importance of cycads and cycad aulacaspis scale is discussed. A taxonomic history of Phaenochilus is provided.